1997
DOI: 10.1046/j.1365-2710.1997.9675096.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of refrigerated and frozen solutions of tropisetron in either polyvinylchloride or polyolefin infusion bags

Abstract: Tropisetron (50 microg/ml) in either 0.9% sodium chloride or 5% dextrose is chemically stable in polyvinylchloride or polyolefin bags for at least 3 months when stored in a refrigerator or in a frozen state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…In both studies, tropisetron hydrochloride was stable for at least 14 days when stored at −20°C, 4°C, and 25°C. 23 , 24 However, in a study with fosaprepitant admixtures, tropisetron hydrochloride was found to be physically incompatible with fosaprepitant because of its alkaline pH value. 25 …”
Section: Discussionmentioning
confidence: 99%
“…In both studies, tropisetron hydrochloride was stable for at least 14 days when stored at −20°C, 4°C, and 25°C. 23 , 24 However, in a study with fosaprepitant admixtures, tropisetron hydrochloride was found to be physically incompatible with fosaprepitant because of its alkaline pH value. 25 …”
Section: Discussionmentioning
confidence: 99%
“…It is the case, 29 drugs described in 20 papers [15,24,[27][28][29][30]32,33,[42][43][44][45]47,52,[55][56][57]59,61,63,76]. The stability for a period of 24 hours at least was described for 17 drugs in 8 papers [22,[26][27][28][29]34,41,43,48].…”
Section: Discussionmentioning
confidence: 99%
“…The final nominal concentrations of dezocine and tropisetron hydrochloride were 0.4 mg/mL and 0.05 mg/mL, respectively. [17,18] The selection of the concentrations of these drugs in our study was based on those used in daily practice. Three polyolefin bags and 3 glass containers containing the dezocine and tropisetron hydrochloride admixture were stored at 4°C or 25°C.…”
Section: Methodsmentioning
confidence: 99%